2019
DOI: 10.3390/molecules24050938
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Aspalathin in Rooibos (Aspalathus linearis) Plant and Herbal Tea Extracts Using Thin-Layer Chromatography

Abstract: Aspalathin, the main polyphenol of rooibos (Aspalathus linearis), is associated with diverse health promoting properties of the tea. During fermentation, aspalathin is oxidized and concentrations are significantly reduced. Standardized methods for quality control of rooibos products do not investigate aspalathin, since current techniques of aspalathin detection require expensive equipment and expertise. Here, we describe a simple and fast thin-layer chromatography (TLC) method that can reproducibly visualize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Biochemical screening of plant samples for specific compounds of interest can represent a cost-limiting factor, since many of these compounds can only be detected using expensive technologies such as HPLC, Near Infrared Spectroscopy (NIS) or Raman Spectroscopy (RS). In this study, high-throughput biochemical screening was completed using thin layer chromatography (TLC) analyses that permitted detection of aspalathin and identification of plant-specific fingerprints [ 50 ]. TLC is a simple and easily scalable method for detection of diverse compounds in plant extracts, herbal products, and foods [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Biochemical screening of plant samples for specific compounds of interest can represent a cost-limiting factor, since many of these compounds can only be detected using expensive technologies such as HPLC, Near Infrared Spectroscopy (NIS) or Raman Spectroscopy (RS). In this study, high-throughput biochemical screening was completed using thin layer chromatography (TLC) analyses that permitted detection of aspalathin and identification of plant-specific fingerprints [ 50 ]. TLC is a simple and easily scalable method for detection of diverse compounds in plant extracts, herbal products, and foods [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thin-layer chromatography was performed on all collected plant samples as described in [ 50 ]. Four plants that differed in their morphological characteristics and in their thin-layer chromatography (TLC) profiles were selected for further biochemical characterization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, fresh leaf material is the material of choice for flow cytometry analyses. For rooibos, once harvested, leaves turn red-brown in a very short period of time, which is mostly due to the degradation of aspalathin [39]. Preliminary flow cytometry tests showed that these tissues do not yield peaks in the histograms.…”
Section: Discussionmentioning
confidence: 99%